Wilson’s Disease: A Review - Amie Vidyani; Fauziah Diayu Retnaningtyas; Ulfa Kholili; Titong Sugihartono; Iswan Abbas Nusi; Poernomo Boedi Setiawan; Ummi Maimunah; Budi Widodo; Husin Thamrin; Muhammad Miftahussurur; Herry Purbayu (Current Internal Medicine Research and Practice Surabaya Journal, 2023)
Wilson’s disease is a disease that results from a genetic disorder that causes copper accumulation. Wilson’s disease has presented challenges for physicians during the last century, but it can be diagnosed and treated over time. Diagnosing Wilson’s disease is challenging for doctors because of its wide range of clinical manifestations and complexity. Studies that can help diagnose Wilson’s disease include a 24-hour copper urine examination and neurological tests, such as a CT scan or MRI, and liver function tests. There is also a scoring system to help medical personnel diagnose this disease. Correct diagnosis and adequate therapy can be provided, such as penicillamine, trientine, zinc, and, most rarely, liver transplantation. It is also necessary to monitor the side effects of treatment and its effectiveness of treatment. When receiving therapy, Wilson’s disease has a better prognosis than if it is not treated.